2020
DOI: 10.1002/pip.3269
|View full text |Cite
|
Sign up to set email alerts
|

Early‐stage identification of encapsulants photobleaching and discoloration in crystalline silicon photovoltaic module laminates

Abstract: Commercially different variants of ethylene‐vinyl acetate (EVA) encapsulants are available in the photovoltaic (PV) market. Photobleaching and discoloration are the two most commonly observed phenomena, and their initiation may be different for different encapsulants. To investigate the EVA encapsulant photobleaching and discoloration, solar cell laminates having different EVA films (UV‐transparent [T], UV‐cut [C], and combination of the two [TC]) were tested in Xenon test chamber. High temperatures are create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…A similar effect is proposed to occur within these doped glasses because of the shifted absorbance. Yellowing and ultimately browning of C‐EVA has been shown to reduce module efficiency by up to 45% within 5 years of installation, 126 whereas, as noted in Section 1, the long‐term in situ performance of T‐EVA in PV modules has not yet been fully investigated—although it is expected to provide superior capabilities to C‐EVA, its yellowing index is nonzero, 17 and hence, enhanced protection of T‐EVA by the cover glass remains a key requirement.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A similar effect is proposed to occur within these doped glasses because of the shifted absorbance. Yellowing and ultimately browning of C‐EVA has been shown to reduce module efficiency by up to 45% within 5 years of installation, 126 whereas, as noted in Section 1, the long‐term in situ performance of T‐EVA in PV modules has not yet been fully investigated—although it is expected to provide superior capabilities to C‐EVA, its yellowing index is nonzero, 17 and hence, enhanced protection of T‐EVA by the cover glass remains a key requirement.…”
Section: Resultsmentioning
confidence: 99%
“…Service lifetimes and efficiencies of solar cell components are limited by solar UV radiation damage, which induces degradation of laminate materials, the most frequently used being ethylene vinyl acetate (EVA), eventually leading to delamination and module failure, 15 although in recent years, ‘transparent EVA’ or T‐EVA, with a UV cut‐off wavelength of ~300 nm, has been developed, 16 reducing this effect. However, discolouration and delamination of T‐EVA can still arise at the backsheet interface in PV modules, as recently discussed by Adothu et al 17 They also demonstrated discolouration and photobleaching of T‐EVA in c‐Si PV module tests, with yellowness indices, following UV exposure, that were approximately one‐quarter those of traditional UV‐cutting EVA (C‐EVA) 17 . Although a significant improvement, the yellowness index of the T‐EVA was still nonzero.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations